Relationship of Maternal Education with Malnutrition in Children Under the Age of Five Years Presented to A Tertiary Care Hospital: Maternal Education with Malnutrition in Children Under the Age of Five Years - Ullah, Akram; Amir, Sabahat; Gul, Ruba; Afridi, Shah Fahad; Zuhra, Fatima; Shah, Sulaiman; Khan, Namrah (Pakistan Journal of Health Sciences, 2026)
Malnutrition remains a major public health problem among children under five years, particularly in developing countries like Pakistan. Maternal education plays a crucial role in determining child nutritional status through its influence on feeding practices, healthcare utilization, and overall child care. Objective: To determine the association between maternal education and the severity of malnutrition among children under five years of age presenting to a Stertiary care hospital. Methods: This cross-sectional study was conducted at Khyber Teaching Hospital, Peshawar, including 282 malnourished children aged 6 months to 5 years. Nutritional status was assessed using WHO Z-scores (WAZ, HAZ, WHZ) and categorized into moderate and severe malnutrition. Maternal education was classified into six levels. Data were analyzed using SPSS version 27.0, and associations were evaluated using Fisher’s Exact tests, with p ≤ 0.05 considered significant. Results: The mean age was 28.4 ± 11.2 months. The prevalence of malnutrition was high, with 54.8% underweight, 48.8% stunted, and 32.4% wasted. Severe malnutrition was common, particularly among children of illiterate mothers, showing significantly higher rates of underweight (65.4%), stunting (75.0%), and wasting (70.0%) (p≤0.002). On multivariable analysis, maternal illiteracy remained a strong independent predictor of underweight (AOR: 4.89), stunting (AOR: 5.73), and wasting (AOR: 4.12), all statistically significant (p<0.001). Higher maternal education showed a protective effect against all forms of malnutrition. Conclusions: Maternal education is associated with reduced severity of childhood malnutrition. Improving female education and implementing targeted nutritional interventions are essential to reduce the burden of malnutrition.